An Analytical Study of Suspension Bridge Collapse Based on the Characteristics of the Eigen Values - Jufriansah, Adi; Pramudya, Yudhiakto; Lazwardi, Ahmad; Khusnani, Azmi; Nurrahman, Arip; Alip, Isma; Wae, Konsenius Wiran; Wahab, Dedi Suwandi (The Indonesian Institute of Science and Technology Research, 2024)
This research discusses an analytical approach to suspension bridge accidents focusing on eigenvalue characteristics. This research uses eigenvalue analysis to explore patterns that may contribute to bridge structural failure. The analysis steps include reducing the model to an uncoupled and linear system, as well as determining homogeneous and non-homogeneous solutions, which helps identify accident-prone patterns. The analysis results also reveal significant differences in dynamic characteristics between safe bridges and those that experience accidents. This research highlights the importance of a deep understanding of eigenvalues in designing, maintaining, and managing suspension bridges. The implication of this research is the development of more effective prevention strategies to improve suspension bridge safety in the future. By analyzing eigenvalues, this research provides deep insight into the factors that influence the stability of suspension bridges. These findings provide a strong foundation for developing recommendations for more effective design, maintenance, and management of suspension bridges. The conclusions of this research can help improve the safety and reliability of suspension bridges worldwide and contribute to civil engineering and infrastructure security.